Sosialisasi Gema Cermat (Gerakan Masyarakat Cerdas Menggunakan Obat) dengan Memasyarakatkan “Tanya 5 O” - Fitria Megawati; Ni Putu Dewi Agustini; I Putu Tangkas Suwantara; Ni Putu Udayana Antari; Gusti Ayu Putu Laksmi Puspa Sari (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Public knowledge of self-medication is crucial, and one of the challenges faced is the lack of awareness regarding this practice. Irrational self-medication can lead to harmful consequences, such as incorrect treatment due to inaccurate self-diagnosis. Contributing factors include biased drug advertisements in the media and inadequate information from healthcare professionals. Community engagement is one of the collaborative sharing programs initiated by the Government, known as the Gema Cermat (Smart Community Using Medicines Movement), which includes the promotion tagline